2020
DOI: 10.2967/jnumed.120.252403
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT-Guided Biopsy of Suspected Lung Lesions Requires Less Rebiopsy Than CT-Guided Biopsy Due to Inconclusive Results

Abstract: Title: PET/CT guided biopsy of suspected lung lesions requires less rebiopsy than CT guided biopsy due to inconclusive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…In our study, we enrolled masses or consolidation larger than 3 cm. In these cases, PET/CT images were necessary to guide biopsy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we enrolled masses or consolidation larger than 3 cm. In these cases, PET/CT images were necessary to guide biopsy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we enrolled masses or consolidation larger than 3 cm. In these cases, PET/CT images were necessary to guide biopsy [17]. Interestingly, even though CNB of lung lesions is a high-risk procedure, but no severe complications developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceci et al 25 recently reported how PET/CT-guided biopsy of lung lesions led to fewer inconclusive biopsies than CT-guided biopsy, confirming how the 18 F-FDG uptake cover a key role in the potential histological characterization. Another recent report by Caruso et al 26 point out the ability of Radiomics CT-texture analysis in differentiating malignant from benign lung nodules with low FDG uptake, enhancing the importance of radiological heterogeneity beyond FDG PET/CT and lung biopsy. In this scenario, future studies are needed to assess if Radiomics features may give more information about the biopsy outcome prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous lung needle biopsy can be guided by different imaging techniques, such as CT [ 2 ], fluoroscopy CT [ 12 ], cone beam CT [ 13 ], positron emission tomography (PET)-CT [ 14 ], or ultrasound in case of superficially located lesions [ 15 ]. The choice of the imaging technique depends on its availability, lesion type and location, patient’s collaboration, and operator’s preferences [ 2 ].…”
Section: Introductionmentioning
confidence: 99%